Fire Safe Interior Surface Finishes : A Selection Guide - Kumar, Rakesh; A. A., Ansari; A., Aravind Kumar (AMC Indian Journal of Civil Engineering, 2021)
The main focus of this article was to mitigate the fire hazards occurring from the internal furnishing materials widely used in buildings. To enhance the safety of life and property inside buildings, internal material selection guide characteristics were developed. The internal furnishing materials used in the buildings were initially characterized as non-combustible and combustible materials based on the ignitability properties of materials as per Indian Standard, IS: 3808 – 1979. The combustible materials were further classified as Class 1 – 4 based on the surface spread of the flame (SSF) as per British standard BS 476 : Part 7. With these specifications and standard test methods, the internal furnishing materials such as gypsum board, rock wool slab, deodar wood, Polyvinylchloride structural foam, Phenol formaldehyde foam, particleboard, rice husk board, and particleboard, etc. were characterized. Recommendations were prepared on their usage of the materials for selection and application at a suitable location, with respect to ceiling height, and any fire-retardant treatment. These internal furnishing materials selections/recommendations guide will help to improve fire safety in buildings.